The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/rnj.140
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Adolescents and Young Adults with Spina Bifida to Adult Healthcare: Initial Findings from a Model Program

Abstract: SBTP is well-received by participants and their parents and may be useful model for other chronic health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 20 publications
(21 reference statements)
0
22
0
Order By: Relevance
“…We have found that the needs of the transition population are complex, multi-factorial and varied. They center on themes of autonomy, mutual respect and expectations that the patient will take on greater independence in their own care 4,20,23 . The process for establishing an adult clinic not only includes identifying a suitable location and adult providers but also recognizing that the best care is delivered in a paradigm that emphasizes holistic lifelong care 4,15,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that the needs of the transition population are complex, multi-factorial and varied. They center on themes of autonomy, mutual respect and expectations that the patient will take on greater independence in their own care 4,20,23 . The process for establishing an adult clinic not only includes identifying a suitable location and adult providers but also recognizing that the best care is delivered in a paradigm that emphasizes holistic lifelong care 4,15,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The capability for transition must be developed over years and involve the patient, family, and care team. In this context, the logistical transfer of care from the pediatric to the adult environment is triggered by an actual chronological age but occurs as a culmination of a carefully developed incremental process 20,23,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transitioning is a challenging time for adolescents, their families and also health care providers (19). Given that adolescence brings with it many challenges of its own (leaving home, moving to university, relationships and starting careers) preparation for clinical transition should commence early in adolescence (20). Inadequate transitioning affects up to 60% of adolescents with complex health needs (21) and the quality of transition processes can vary according to the underlying health issues and the specialists involved (22).…”
Section: Discussionmentioning
confidence: 99%
“…In our survey, one respondent commented that since commencing an adult spina bifida clinic 11 years previously, the two top issues encountered were urological and hydrocephalus-related. A model program for transitioning patients with spina bifida supports the notion that transition should be a multidisciplinary process involving social workers, physiotherapists, nurses, community paediatric and adult providers as well patients and their parents as well (1,20). Multidisciplinary clinics exist in the paediatric setting, but may be more fragmented in the adult sector.…”
Section: Discussionmentioning
confidence: 99%